The Predictive Role of Psychological Well-Being and Social Safeness and Pleasure on Tendency of Psychological Stigma - Deniz, Derya; YILDIRIM, MELİS SERAY ÖZDEN (My University, 2018)
Stigmatization is based on negative beliefs and prejudices that starts with labeling and ends with discrimination and exclusion. In most of the researches stigma tendency was associated with illnesses and disabilities but it can be experienced at any time in life. Stigma tendency of people can be related with psychological properties. On this basis the aim of this study is to determine the predictive role of psychological well-being and social safeness and pleasure on tendency of psychological stigma. The research group was conducted by 200 adults. Data was collected with Demographical Information Form, Stigma Scale, Psychological Well-Being Scale, Social Safeness and Pleasure Scale. The findings indicated that psychological well-being had a significant predictive role on tendency of psychological stigma but social safeness and pleasure didn’t predict stigma tendency. The findings of the research were discussed with regard to relevant literature and suggestions were offered regarding the findings of the study.
Keywords: Psychological well being; social safeness; psychological stigma; pleasure